Histochemical assays of secretory trichomes and the structure and content of mineral nutrients in Rubus idaeus L. leaves - Chwil, Mirosława (Protoplasma, 2019)
Leaves of Rubus idaeus are a raw material, ingredients of herbal blend, and a source of antioxidants. There are no data concerning histochemistry of trichomes, and little is known about the leaf structure of this species. The aim of this study was to determine the histochemistry of active compounds and the structure of glandular trichomes, micromorphology, anatomy, and ultrastructure of leaves as well as content of elements. To determine the histochemistry of glandular trichomes, different chemical compounds were used. The leaf structure was analysed using light, scanning, and transmission electron microscopes. The content of elements was determined with atomic absorption spectrometry, and the microanalysis of the epidermis ultrastructure was carried out with a transmission electron microscope equipped with a digital X-ray analyser. In glandular trichomes, polyphenols, terpenes, lipids, proteins, and carbohydrates were identified. The main elements in the ultrastructure of the epidermis were Na, Mo, Se, Ca, and Mg. In dry matter of leaves, K, Mg, Ca, P, and Fe were dominant. Infusions from leaves are safe for health in terms of the Cd and Pb concentrations. Leaves can be a valuable raw material. Non-glandular trichomes prevent clumping of mixed raw materials in herbal mixtures.